Requirements for reflection in the critical care environment - Celia J. Filmalter; Tanya Heyns (AOSIS, 2015)
Background: Reflection is recognised as an important method for practice development. The importance of reflection is well documented in the literature, but the requirements for reflection remain unclear. Objectives: To explore and describe the requirements for reflection in the critical care environment as viewed by educators of qualified critical care nurses. Method: A focus group interview was conducted to explore and describe the views of educators of qualified critical care nurses regarding requirements for reflection in the critical care environment. Results: The themes that emerged from the focus group were buy-in from stakeholders -management, facilitators and critical care nurses, and the need to create an environment where reflection can occur. Conclusion: Critical care nurses should be allowed time to reflect on their practice and be supported by peers as well as a facilitator in a non-intimidating way to promote emancipatorypractice development.